Peran Dinas Tenaga Kerja dalam Pembangunan Manusia di Kabupaten Mamberamo Tengah - Norika Aud; Abner H. Bajari; Ari Juliyana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to describe and analyze the role and factors that support and inhibit the operation of the labor office in human development in Central Mamberamo Regency. The research method used in this study is descriptive qualitative with data collection using interviews, observations and documentation. While the analysis techniques are Data Display, Data Condensation, Drawing and Verification Conclusions. The results of the study indicate that: The Role of the Manpower Office in Human Development in Central Mamberamo Regency, which includes: Stabilizer, Innovator, Modernizer, Pioneer and Implementer has been running well in order to support human development related to the field of employment. Supporting factors for the Role of the Manpower Office are the existence of clear legal regulations, accurate functions and openness of information and the availability of a budget. While the inhibiting factors are internal factors in the form of a lack of initiative from the Central Mamberamo Regency Manpower Office in utilizing existing facilities and also external factors that include the low level of education of job seekers, lack of expertise and skills and limited job opportunities. Keywords: Department of Manpower, Human Development